A preliminary study on the formulation of indicators and definitions of mathematical bitterness related to teacher treatment - Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto; Yanti Yanti (Jurnal Elemen, 2023)
Teachers are responsible for helping students to understand and admire subjects, which means they need first to appreciate what is supposed to be taught. Meanwhile, some intern teachers detest several subjects due to the unpleasant treatment received from their tutors. This study intends to clarify the definition of mathematical bitterness and develop its indicators. The respondents were seven third-year students at Pelita Harapan University, Indonesia. Data were collected using questionnaires and interviews and analyzed through descriptive qualitative with a phenomenological approach. The results showed that the indicators of bitterness in mathematics sprang from the following, 1) having experienced unpleasant treatment from a mathematics teacher for a long time, 2) having a negative view of mathematics, 3) feeling untalented in mathematics, 4) viewing the mathematics teacher as unfriendly, 5) poor mathematics learning performance, and 6) having high mathematical anxiety. The proposed definition of bitterness is a negative perception of mathematics that is built from the accumulation of past experiences that affect the student’s response to this subject. Hence, further studies are needed to provide solutions that help to heal students of their math bitterness.